Skin dose evaluation after accidental contamination during Mo-99 extraction process. (May 2017) - Abdelhady, Amr
Highlights: The study aims to calculate the skin dose after contamination during 99 Mo extraction. Varskin4 code was used to evaluate the skin dose rate for each stage of extraction. The calculated skin dose rates are very high after contamination for each stage. Permissible times to the onset of skin injury were calculated for each stage.